Improving efficiency and product quality by optimizing methanol purification in biodiesel plant: Addressing abnormalities in distillation column performance - Anggara Dwita Burmana; Yacine Benguerba; Filicia Wicaksana; Vikram Alexander; Silvia Nova; Taslim Taslim; Iriany Iriany (International Journal of Thermofluids)
The distillation column plays a critical role in purifying the water–methanol mixture, with methanol being reused as a reactant in biodiesel production. However, corrosion-induced disruptions in the distillation system can lead to liquid build-up on trays, excessive vapor accumulation at the top, and foaming, which are categorized as abnormal conditions. This study aims to discuss normal and abnormal conditions in the separation process of the water–methanol mixture using a distillation column in a biodiesel plant. The novelty of this research lies in analyzing the performance of methanol-water separation in a distillation column within a biodiesel plant using lauric acid, identifying the causes of performance failure, and providing practical insights to enhance process efficiency. Data were collected via the distributed control system, capturing flowrate, temperature, pressure, and composition under both normal and abnormal conditions, with an emphasis on the effects of corrosion and column performance. The results obtained under abnormal conditions, the side-draw temperature rises to 85 °C (from 78 °C), and the distillate temperature drops to 63 °C (from 74 °C) due to excessive foaming. Methanol mass purity in the distillate decreases to 88 %, and side-draw purity falls to 61 %. The pressure difference also narrows to 0.2 bar (compared to 0.3 bar in normal conditions), and water purity at the bottom decreases to 85 %, well below the target of 99.7 %. Regular inspections of the distillation column are essential. Implementing advanced monitoring and control systems can further optimize distillation column performance and ensure the consistent quality of the final product.